Inspector Wallander's angst, social change and the reconfiguration of Swedish exceptionalism. (July 2015) - Pratt, John; McLean, Thomas
This article examines the extent to which changes in Swedish values and culture are undermining what has come to be known as the penal exceptionalism of that society. It does this by contrasting the two very different pictures of Swedish society that are to be found in the detective novels of Maj Sjöwall and Per Wahlöö, set in the 1960s and early 1970s, and those of Henning Mankell, set in the 1990s onwards. Notwithstanding the extensive social change we find reflected in them, it is argued that Sweden's penal exceptionalism has been reconfigured rather than swept aside. It largely remains intact for those on the legitimate side of the barriers and divisions that mass immigration has constructed around it, but those whose ethnicity denies them this status are likely to find themselves excluded from it.